The Video Interaction Guidance approach applied to teaching communication skills in dentistry. (20th April 2015) - Quinn, S.; Herron, D.; Menzies, R.; Scott, L.; Black, R.; Zhou, Y.; Waller, A.; Humphris, G.; Freeman, R.
Abstract: Purpose: To examine dentists' views of a novel video review technique to improve communication skills in complex clinical situations. Materials and Methods: Dentists ( n  = 3) participated in a video review known as Video Interaction Guidance to encourage more attuned interactions with their patients ( n  = 4). Part of this process is to identify where dentists and patients reacted positively and effectively. Each dentist was presented with short segments of video footage taken during an appointment with a patient with intellectual disabilities and communication difficulties. Having observed their interactions with patients, dentists were asked to reflect on their communication strategies with the assistance of a trained VIG specialist. Results: Dentists reflected that their VIG session had been insightful and considered the review process as beneficial to communication skills training in dentistry. They believed that this technique could significantly improve the way dentists interact and communicate with patients. The VIG sessions increased their awareness of the communication strategies they use with their patients and were perceived as neither uncomfortable nor threatening. Discussion: The VIG session was beneficial in this exploratory investigation because the dentists could identify when their interactions were most effective. Awareness of their non‐verbal communication strategies and the need to adopt these behaviours frequently were identified as key benefits of this training approach. One dentist suggested that the video review method was supportive because it was undertaken by a behavioural scientist rather than a professional counterpart. Conclusion: Some evidence supports the VIG approach in this specialist area of communication skills and dental training.